The effect of repetition on textual coherence in the caliber of poetry for IBN Tabataba - Khayriyah Echresh Joma Hamidi Hasoni ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Repetition is one of the important tools in textual linking and through it a way is made to connect the parts of the sentences, confirming the intended meaning and moving to a new meaning, this is formed through the semantic dimension of it, and to clarify the validity of this claim, this study was conducted in the caliber of poetry for " IBN Tabataba, where It included two topics, the first one dealt with introducing the author and the book, and the second one included an applied study on examples from the book, which we chose, not exclusively, and we have shown in them the types of repetition and the accompanying effect in form and significance…